Comparative Analysis of Pre- and Post-COVID-19 Determinants of Basic Handwashing Facility in Bangladesh: A GLMM Study Using BDHS 2017-18 and 2022 Data: Comparative Analysis of Pre- and Post-COVID-19 Determinants of Basic Handwashing Facility in Bangladesh (Dhaka University Journal of Science, 2025)
This study sought to identify key determinants of basic handwashing facility in Bangladesh before and after COVID-19. Data from the Bangladesh Demographic and Health Surveys (BDHS) for 2017–18 and 2022 were analyzed using a Generalized Linear Mixed Model (GLMM) that accounted for fixed effects and cluster-level variations. The prevalence of basic handwashing facility increased from 41.3% to 59.7%. Before COVID-19, significant determinants included division, place of residence, the sex and age of the household head, household size, partner’s education, working status, media exposure, and the age and education of mothers with children under five. After the pandemic, critical factors shifted to the household head’s age, partner’s education, media exposure, women empowerment, wealth index, and the age and education of mothers. These findings suggest that the pandemic accelerated improvements in hand hygiene, emphasizing the need for targeted public health interventions informed by socio-demographic factors.Dhaka Univ. J. Sci. 73(2): 107-117, 2025 (July)